Recombined human endostatin (Endostar) enhances cisplatin delivery and potentiates chemotherapy by decompressing colorectal cancer vessels - Zhao, Xiaoxu (Int J Clin Exp Pathol, 2017)
Tumor vessels are continuously compressed by solid stress from tumor interstitial matrix, contributing to limited vessel perfusion and oxygen delivery, in which, Collagen plays an important role in transmitting the solid stress to tumor vessels. Therefore, it is urgent to explore novel drugs targeting solid stress, which can increase vessel perfusion as well as drug delivery in cancers. We demonstrate that recombined human endostatin (Endostar) could decrease colorectal cancer associated ﬁbroblasts (CAF) density, reduces tumor stromal collagen I production, and decrease the expression of profibrotic signals, including vascular endothelial growth factor (VEGF), connective tissue growth factor (CTGF) as well as transforming growth factor β1 (TGF-β1). Consequently, Endostar was able to relieve solid stress in tumor, leading to increased vessel perfusion. Following this mechanism, oxygen as well as cisplatin delivery were promoted by Endostar, leading to alleviated hypoxia and chemotherapy sensitivity in colorectal cancer model. Taken together, Endostar could be utilized as a potential agent to effectively decompress tumor vessels and to inhibit tumor growth through its therapeutic function.